\(\dfrac{x-7}{x+6}=\dfrac{x+3}{x-5}\)
\(\Leftrightarrow x^2-12x+35=x^2+9x+18\)
\(\Leftrightarrow-21x=-17\)
hay \(x=\dfrac{17}{21}\)
\(\dfrac{x-7}{x+6}=\dfrac{x+3}{x-5}\)
\(\Leftrightarrow x^2-12x+35=x^2+9x+18\)
\(\Leftrightarrow-21x=-17\)
hay \(x=\dfrac{17}{21}\)
Tìm x, biết
a)\(\dfrac{1}{2}\)x\(x\)-\(\dfrac{7}{3}\)=\(\dfrac{-5}{6}\)+\(\dfrac{3}{4}\)x\(x\)
b)\(\dfrac{4}{5}\)x\(x\)-\(\dfrac{6}{5}\)=\(\dfrac{1}{2}\)+\(\dfrac{3}{2}\)x\(x\)
c)\(\dfrac{2}{5}\)x(3x\(x\)+\(\dfrac{3}{4}\))=\(1\dfrac{1}{5}\)-\(\dfrac{1}{3}\)x\(x\)
d)2x(3x\(x \)+\(\dfrac{3}{4}\))+\(\dfrac{4}{5}\)=\(\dfrac{1}{2}\)-2x\(x\)
Bài 4: tìm x:
a) \(\dfrac{4}{3}\) + (1,25 - x) = 2,25
b) \(\dfrac{17}{6}\) - (x - \(\dfrac{7}{6}\) ) = \(\dfrac{7}{4}\)
c) 4 - (2x + 1) = 3 - \(\dfrac{1}{3}\)
bài 15:
a) (\(\dfrac{-2}{3}\))9 : x = (\(\dfrac{-2}{3}\))
b) x : (\(\dfrac{4}{9}\))5 = (\(\dfrac{4}{9}\))4
c) (x + 4)3 = -125
d) (10 - 5x)3 = 64
e) (4x + 5)2 = 81
Bài 16:
a) 4 - \(1\dfrac{2}{5}\) - \(\dfrac{8}{3}\)
b) -0,6 - \(\dfrac{-4}{9}\) - \(\dfrac{16}{15}\)
c) \(-\dfrac{15}{4}\) . (\(\dfrac{-7}{15}\)) . (\(-2\dfrac{2}{5}\)
Gi ải gấp giúp mình ạ, mình rất cần gấp
Tìm x :
a, \(\dfrac{11}{12}\) - (\(\dfrac{2}{5}\) +x) = \(\dfrac{2}{3}\) b, x+\(\dfrac{2}{3}\) =\(\dfrac{3}{5}\) - \(\dfrac{-1}{6}\) c, x-[\(\dfrac{17}{2}\) -(\(\dfrac{-3}{7}\) + \(\dfrac{5}{3}\) )]=\(\dfrac{-1}{3}\)
d,\(\dfrac{9}{2}\) - [\(\dfrac{2}{3}\) - (x+\(\dfrac{7}{4}\) )] =\(\dfrac{-5}{4}\)
Mọi người giúp mình nha
\(b,\dfrac{x}{2}-\left(\dfrac{3x}{5}-\dfrac{13}{5}\right)=-\left(\dfrac{7}{5}+\dfrac{7}{10}.x\right)\)
\(c,\dfrac{2x-3}{3}+\dfrac{-3}{2}=\dfrac{5-3x}{6}-\dfrac{1}{3}\)
\(d,\dfrac{2}{3x}-\dfrac{3}{12}=\dfrac{4}{5}-\left(\dfrac{7}{x}-2\right)\)
\(e,2\left(x-1\right)=\left(x-1\right)^2\)
Tìm x:
a) \(\dfrac{11}{12}\) - (\(\dfrac{2}{5}\) + \(\dfrac{3}{4}\)x) \(\dfrac{2}{3}\)
b) \(\dfrac{-2}{5}\) + \(\dfrac{5}{3}\) . (\(\dfrac{3}{2}\) - \(\dfrac{4}{15}\)x) = \(\dfrac{-7}{6}\)
c) \(\dfrac{1}{2}\) + \(\dfrac{3}{4}\)x = \(\dfrac{1}{4}\)
\(\dfrac{x+5}{2005}\)+\(\dfrac{x+6}{2004}\)+\(\dfrac{x+7}{2003}\)=-3
Tìm x :
1) \(\left(-0,75x+\dfrac{5}{2}\right).\dfrac{4}{7}-\left(-\dfrac{1}{3}\right)=-\dfrac{5}{6}\)
2) \(\left(4x-9\right)\left(2,5+\dfrac{-7}{3}x\right)=0\)
3) \(\left|x-\dfrac{3}{4}\right|-\dfrac{1}{2}=0\)
4)\(\left(\dfrac{3}{5}-\dfrac{2}{3}x\right)^3=\dfrac{-64}{125}\)
\(a,\left|x+\dfrac{1}{5}\right|-4=-2\)
\(b,-\dfrac{15}{12}x+\dfrac{3}{7}=\dfrac{6}{5}x+-\dfrac{1}{2}\)
Bài 1: Tìm x; y ϵ \(ℤ\)
a) 2x - y\(\sqrt{6}\) = 5 + (x + 1)\(\sqrt{6}\)
b) 5x + y - (2x -1)\(\sqrt{7}\) = y\(\sqrt{7}\) + 2
Bài 2: So sánh M và N
M = \(\dfrac{\dfrac{3}{4}+\dfrac{3}{5}+\dfrac{3}{7}-\dfrac{3}{11}}{\dfrac{6}{4}+\dfrac{6}{5}+\dfrac{6}{7}-\dfrac{6}{11}}\)
N = \(\dfrac{\dfrac{2}{3}+\dfrac{2}{5}-\dfrac{2}{7}-\dfrac{2}{11}}{\dfrac{6}{2}+\dfrac{6}{5}-\dfrac{6}{7}-\dfrac{6}{11}}\)
Bài 3: Chứng minh:
\(\dfrac{1}{2!}+\dfrac{1}{3!}+\dfrac{1}{4!}+...+\dfrac{1}{2023!}< 1\)